Hubungan Antara Pola Asuh Ibu dengan Kejadian Stunting di Wilayah Kerja Puskesmas Oesapa - Nelson Keba Rangga Suba; Lewi Jutomo; Marselinus Laga Nur (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Stunting is a nutritional problem that is still a global problem. Stunting is a condition of growth failure caused by a lack of nutritional intake in the first 1000 days of life. This study was conducted to determine the relationship between Mother's Parenting Patterns and the Incidence of Stunting in Toddlers at the Oesapa Health Center. The type of research used is analytical observation with a case control study design, which is an analytical survey study that tells about how risk factors with a retrospective approach are studies that try to look back, meaning that data collection starts from the effects or consequences that have occurred. The population of this study is. The population in this study were toddlers aged 12-59 months with a research sample of 98 people. The collected data were analyzed using the chi-square test. The results of the bivariate analysis of feeding practices (p-value <0.001) showed a relationship between the use of health services (p-value = <0.005) related to clean and healthy living behavior (p- value = <0.005) related to a history of infectious diseases (p-value = <0.005) related between maternal parenting patterns and the incidence of stunting in the Oesapa health center work area.